An Introduction to Gender in Feminine Literature and Criticism (Journal of the College of Education for Women, 2019)
The Gender study is consider one of the concepts which the Postmodernism reachedafter the end of Modernism, where the first one has limited the criticism study choices beforethe second after closed many doors of subjects which was enriched by researches.It is pretty clear that the root of this concept belongs to the Linguistics which providedthe Criticism with a countable reasons of it is growth.The attention in the study of gender in Feminine Literature and Criticism increased inArabic studies since the early years of twenty one century, so this research is presented to bean introduction to this subject which could pave the way to more studies.In addition to the Gender studies this research deals with another concept whichreceived a considerable attention from the Arabic Criticism, it is the Feminist Criticism,whether it was affiliated to the literary or cultural criticism.In the first Part, the research tries to present the gender term in it is lingual aspect ,following the criterion which the bilateral Man/Woman was built according to, and refer toone of Julia Cristivas novels, while the second part identify the feminist criticism andfollowing up this theory.